UPAYA KEPEMIMPINAN CAMAT DALAM MENINGKATKAN KESADARAN MASYARAKAT UNTUK MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB) DI KECAMATAN MEDAN AMPLAS KOTA MEDAN - Kelvin Prayoga; Dara Aisyah (Smart Education, 2023)
The lack of public trust in a leader is the root of the existing problems, the decline in public awareness to pay Taxes on Land and Buildings (PBB) is caused by a lack of socialization and efforts given by the government to the people in PBB. The lack of public awareness of paying PBB is evidenced by the PBB realization data which does not reach the target every year. Where from 2020 to 2022 it was recorded that the Medan Amplas District in the realization of PBB revenue did not reach the target. This study aims to analyze and describe the efforts of the Camats leadership in increasing public awareness to pay PBB. The research method used is descriptive with a qualitative approach. Data collection was carried out through interviews, observation and documentation. The data obtained were then analyzed qualitatively using the Trust and Leadership Theory of Stephen P. Robbins. The results showed that the sub-district heads lack of effort in providing counseling to the community,the sub-district heads figure was not good in the eyes of the community, The value of integrity shown by the camat is not so good, The character of the Camat in terms of benevolence is still not maximally felt by the community. Finally, the camats ability to influence the community is still minimal.